Influence of aging process and restoration thickness on the fracture resistance of provisional crowns: A comparative study - Majed M. Alsarani (Saudi Dental Journal)
Background: The advancement of digital dentistry enhanced the fabrication of indirect provisional restorations utilizing durable materials, yet the performance of provisional crowns fabricated with various techniques, and different thickness remains unknown. Thus, this in-vitro study aimed to evaluate the influence of restoration thickness and aging on the fracture behavior of provisional crowns fabricated using different techniques. Methods: A dentiform maxillary first molar was prepared using a highly filled epoxy resin material to construct identical die replicas. Four groups of provisional crowns were fabricated: Group 1 was milled at 1.5 mm occlusal thickness; Group 2 was milled at 0.9 mm thickness; Group 3 was 3D-printed at 1.5 mm occlusal thickness; and Group 4 was 3D-printed at 0.9 mm occlusal thickness. Eight crowns from each group were subjected to a thermocycling process for 5000 cycles between baths held at 5 °C and 55 °C with a dwell time of 30 s and transfer time of 5 s. All crowns (aged and non-aged (control)) were loaded for fracturing using a universal testing machine at a 0.5 mm/min crosshead speed. Data were analyzed using a two-way analysis of variance and multiple comparisons at (α = 0.05). Results: The maximum mean force load was found in the non-aged milled group (M1.5) at 1706.36 ± 124.07 N; the minimum mean force load was recorded for the aged 3D-printed group (3D0.9) at 552.49 ± 173.46 N. A significant difference was observed before and after thermocycling (p < 0.01). Conclusion: Computer-aided design and manufacture of milled provisional crowns is superior to 3D-printed crowns for fracture resistance.